Evaluative Language in Heritage Exploration: A Cultural Approach to Tourism Discourse Analysis - Riyadi Santosa; Rara Sugiarti; Tri Wiratno; Djatmika; Agus Hari Wibowo (Script Journal: Journal of Linguistics and English Teaching, 2026)
Abstract Background: This article presents a discourse analysis of online heritage tourism posts about archaeological and cultural tourist destinations in Surakarta. The objective is to examine the use of evaluative language in cultural contexts for the promotion of local attractions to the international audience. Methodology: The sample texts, selected from two prominent tourism websites (www.lonelyplanet.com and www.javaheritagetour.com), are analyzed through the lens of Appraisal theory, complemented with SFL's concept of Register and Genre. Findings: The results demonstrate that the deployment of evaluative linguistic resources serves not only to promote destinations but also to represent specific cultural and social processes. The discourse on Surakarta's heritage tourism places emphasis on the city's archaeological and cultural significance through Monoglossic language, presenting factual, reactive evaluations that enhance focalization on heritage sites but overlook broader socio-economic and political dimensions, limiting alternative angles and inclusivity. Conclusion: The paper concludes by discussing potential reasons for the evaluative pattern and providing several implications for online heritage tourism cultural communication. Originality: The paper not only discusses conservation, traditions, site management, and visitor experiences, but also applies Appraisal analysis, SFL Genre mapping, and an extended Cultural Approach to Discourse applied to Surakarta's online heritage promotion.